2021
DOI: 10.1371/journal.pntd.0009065
|View full text |Cite
|
Sign up to set email alerts
|

High performance dengue virus antigen-based serotyping-NS1-ELISA (plus): A simple alternative approach to identify dengue virus serotypes in acute dengue specimens

Abstract: Dengue hemorrhagic fever (DHF) is caused by infection with dengue virus (DENV). Four different serotypes (DENV1-4) co-circulate in dengue endemic areas. The viral RNA genome-based reverse-transcription PCR (RT-PCR) is the most widely used method to identify DENV serotypes in patient specimens. However, the non-structural protein 1 (NS1) antigen as a biomarker for DENV serotyping is an emerging alternative method. We modified the serotyping-NS1-enzyme linked immunosorbent assay (stNS1-ELISA) from the originally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…Roltgen et al (2018) developed an ELISA capable of distinguishing four DENV serotypes [ 48 ]. Similar ELISAs were also developed by other groups [ 40 , 41 ]. ELISAs have advantages in quantification, but immunochromatographic tests have the advantage of convenience for individual tests of a small number of samples [ 33 ].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Roltgen et al (2018) developed an ELISA capable of distinguishing four DENV serotypes [ 48 ]. Similar ELISAs were also developed by other groups [ 40 , 41 ]. ELISAs have advantages in quantification, but immunochromatographic tests have the advantage of convenience for individual tests of a small number of samples [ 33 ].…”
Section: Discussionmentioning
confidence: 73%
“…The prevalence of these amino acid sequence differences in various geographical areas should also be determined. Previous studies showed variations in sensitivity and specificity depending on the collection date after the onset of illness, viral characteristics, and heterotypic DENV infection in NS1 DENV-specific detection using clinical specimens [ 40 , 41 , 42 , 43 , 44 ]. These factors might have also played a role in the cross-reactivity observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The serotyping NS1 microplate ELISA was developed as described [ 22 ]. Briefly, each plasma sample (1:5 dilution) was added to four wells pre-coated with the pan-serotype capture antibody (2E11).…”
Section: Methodsmentioning
confidence: 99%
“…Biotinylated serotype-specific antibodies were added to each well separately. In some cases, an additional assay using the antibody pair 2E11/5F3 (for DENV1 and DENV3 subcomplex) was used to increase sensitivity of the assay [ 22 ]. Positive samples were classified when the assay OD reading exceeded twice the value of the negative plasma control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation